Patterns of dendritic cell and monocyte subsets are associated with disease severity and mortality in liver cirrhosis patients - Chandra Chiappin Cardoso (Nature Portfolio, 2021)
Abstract Liver cirrhosis is often complicated by an immunological imbalance known as cirrhosis-associated immune dysfunction. This study aimed to investigate disturbances in circulating monocytes and dendritic cells in patients with acute decompensation (AD) of cirrhosis. The sample included 39 adult cirrhotic patients hospitalized for AD, 29 patients with stable cirrhosis (SC), and 30 healthy controls (CTR). Flow cytometry was used to analyze monocyte and dendritic cell subsets in whole blood and quantify cytokines in plasma samples. Cirrhotic groups showed higher frequencies of intermediate monocytes (iMo) than CTR. AD patients had lower percentages of nonclassical monocytes than CTR and SC. Cirrhotic patients had a profound reduction in absolute and relative dendritic cell numbers compared with CTR and showed higher plasmacytoid/classical dendritic cell ratios. Increased plasma levels of IL-6, IL-10, and IL-17A, elevated percentages of CD62L+ monocytes, and reduced HLA-DR expression on classical monocytes (cMo) were also observed in cirrhotic patients. Patients with more advanced liver disease showed increased cMo and reduced tissue macrophages (TiMas) frequencies. It was found that cMo percentages greater than 90.0% within the monocyte compartment and iMo and TiMas percentages lower than 5.7% and 8.6%, respectively, were associated with increased 90-day mortality. Monocytes and dendritic cells are deeply altered in cirrhotic patients, and subset profiles differ between stable and advanced liver disease. High cMo and low TiMas frequencies may be useful biomarkers of disease severity and mortality in liver cirrhosis.